2018
DOI: 10.3389/fnbeh.2018.00196
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Cognitive and Neuromotor Rehabilitation in Multiple Sclerosis: A Pragmatic Study

Abstract: Background: Few studies examined the effects of combined motor and cognitive rehabilitation in patients with multiple sclerosis (MS). The present prospective, multicenter, observational study aimed to determine the efficacy of an integrated cognitive and neuromotor rehabilitation program versus a traditional neuromotor training on walking, balance, cognition and emotional functioning in MS patients.Methods: Sixty three MS patients were selected and assigned either to the Integrated Treatment Group (ITG; n = 32… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 74 publications
(79 reference statements)
3
19
0
Order By: Relevance
“…In addition, these results are in accordance with previous results showing that EE had an anti-anhedonic effect via induction of BDNF in the prefrontal cortex during the early life (Angelucci et al, 2005;Chu et al, 2018;Yu and Chen, 2011). Furthermore, MS patients that received and integrated cognitive and motor rehabilitation presented positive effects in emotional aspects such as depression in addition to cognitive and motor rehabilitation (Barbarulo et al, 2018;Jimenez-Morales et al, 2017). In addition, in this study, EE enhanced short term memory as demonstrated by improvement of the performance in the NOR test.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In addition, these results are in accordance with previous results showing that EE had an anti-anhedonic effect via induction of BDNF in the prefrontal cortex during the early life (Angelucci et al, 2005;Chu et al, 2018;Yu and Chen, 2011). Furthermore, MS patients that received and integrated cognitive and motor rehabilitation presented positive effects in emotional aspects such as depression in addition to cognitive and motor rehabilitation (Barbarulo et al, 2018;Jimenez-Morales et al, 2017). In addition, in this study, EE enhanced short term memory as demonstrated by improvement of the performance in the NOR test.…”
Section: Discussionsupporting
confidence: 91%
“…. Related to MS patients, it was demonstrated that physical exercise and cognitive rehabilitation enhanced cognitive function in patients (Barbarulo et al, 2018;Jimenez-Morales et al, 2017). This work provides evidence that EE could be regarded as an intervention to improve cognitive function and reduce anxiety-like behaviour.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An integrated approach with cognitive and motor training has demonstrated to be associated with improvements not only in cognitive and motor performance but also in mood ( 66 ). Constant repetition of the same movements, as occurs in CR, might result in the patient being less engaged and motivated, which will affect therapy adherence and ultimately reduce rehabilitation effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Such an approach often reflects the clinical reality of PMS where multiple neurological difficulties rather than an isolated problem must be addressed simultaneously. While a powered joint CR and exercise clinical trial has yet to be done in people with MS of any disease course there is tentative evidence from three small studies in people with RRMS that this approach may be more beneficial than either intervention alone [15][16][17]. Thus, a methodologically rigorous, well-powered study is needed now in PMS specifically in an effort to inform clinical practice.…”
Section: Introductionmentioning
confidence: 99%